Geriatric medicine and long-term care insurance - Yokono, Koichi; Song, Xiuzhen; Sakurai, Takashi (Nihon Rōnen Igakkai zasshi, 2004)
Long-term care insurance (LCI) started from April 2000 in Japan. LCI now occupies a central position in the health care of the aged. We reviewed all original papers and reports on LCI published in 1996-2002. At the end of 2002, we searched for papers on LCI in a computer database using the keyword of LCI, and found 3, 606 papers. Authors and contents of each paper were categorized using 54 kinds of keywords. Frequent authors were government agencies, care managers, physical therapists, and physicians. When we analyzed these papers according to the places where LCI was used, more than 50% of reports concerned LCI at home. Most frequent keywords were Government/LCI system, Regional health, Physician' assessment and grades for care, Care management, Care manager, and Rehabilitation. Care manager was less observed after the start of LCI. In contrast, the use of keywords including Care service, Dementia, Geriatric syndrome, Nurse, Institutional medicine, Hospital care, Medicine for the aged, Terminal care, Dialysis therapy, Abuse of the aged, and Caregiver burden were increased after LCI. At the beginning of LCI, main concerns are on the new LCI system. However, more individual issues in the care of the aged are now discussed. New issues such as Abuse of the aged and Caregiver burden have been recently raised. From these observations, the role of geriatric medicine seems also to be changing after the induction of LCI. We would now contribute actively to crucial aspects of LCI, such as comprehensive assessment of the aged, functional medical network with care staffs, and new therapeutic approaches to each geriatric syndrome.